THE IMPORTANCE OF THEORETICAL AND METHODOLOGICAL APPROACHES IN DEVELOPING THE DEONTOLOGICAL POSITION OF FUTURE TEACHERS OF THE SUBJECT “TARBIYA” - Shodiyeva Ranokhon Abdumajid qizi (TADQIQOTLAR, 2026)
Abstract. This article analyzes the importance of theoretical and methodological approaches in developing the deontological position of future teachers of the subject “Tarbiya”. The study is based on a conceptual-analytical method. It examines deontological, axiological, competence-based, personality-oriented, activity-based, reflective and communicative approaches as methodological foundations for forming professional duty, ethical responsibility and pedagogically justified behavior.